Developing a harvesting plan for forested areas under the risk of winter storm damage - Akay, Abdullah Emin; Taş, D. (Transilvania University of Brasov, 2017)
Timber harvesting activities become more complicated after winter storm damages. The risk of storm damage can be estimated based on various factors such as stand structure, topographical characteristics, climatic parameters, and soil type. In this study, a GIS-integrated Analytical Hierarchy Process (AHP) was used to develop a timber harvesting plan based on a previously generated storm damage risk map, terrain conditions, and soil type. The study was implemented in Kütahya region where serious winter storm damages occurred in winter of 2015. The results indicated that the farm tractor logging was suitable for 40.5% of the area, while the chute system was appropriate for 35.5% of the area.
Keywords: AHP; Storm risk map; Timber harvesting plan; Winter storm damage